ChemInform Abstract: Synthesis of Silica Supported Perchloric Acid Nanoparticles (HClO4—SiO2 NPs): Efficient Synthesis of Biscoumarin Derivatives in Water. Issue 34 (1st August 2013) - Sadeghi, Bahareh
Abstract Biscoumarin derivatives (III) and (V) are obtained in a simple and efficient reaction between aromatic aldehydes (II) or phenylglyoxals (IV) and 4‐hydroxycoumarin (I).